DIAGNOSTIC ACCURACY OF DOPPLER ULTRASOUND IN COMPARISON WITH VENOGRAPHY IN THE DIAGNOSIS OF VARICOSE VEINS OF THE LEGS: Diagnostic Approach of Varicose Veins of the Legs - Ihsan, Maj Hussain Rashid; Saeed, Muhmmad; Ilyas, Muhammad; Ghani, Naureen (Pakistan Armed Forces Medical Journal, 2010)
Objective: To determine the diagnostic accuracy of Doppler ultrasound in the diagnosis of varicose veins of legs using venography as gold standard in picking up deep vein thrombosis. Study Design: Prospective validation study. Place and Duration of study: Six months, 01 Apr -30 Sep 2006 at Radiology Department, Combined Military Hospital, Quetta. Patients and Methods: Fifty cases were included in study, fulfilling the inclusion and exclusion criteria. The patients sampled were referred by surgeons from out patients department. Results: The sensitivity of Doppler was 75 %, specificity 100% and accuracy 98% in picking up deep venous thrombosis (DVT). For the detection of incompetent perforators/reflux disease, at spheno-femoral junction the sensitivity of Doppler ultrasound was 85.7%, specificity 95% and accuracy 94%. At spheno-popliteal junction the sensitivity of Doppler ultrasound was 70%, specificity 100% and accuracy 76 %. Conclusion: Patients with varicose veins of legs should be evaluated first with Doppler ultrasound. Venography remains the examination of choice when absolute determination of the presence and extent of thrombus is needed, for the determination of the reflux disease level in obese patients, in patients with severe leg edema or in patients in whom results of Doppler ultrasound is equivocal or negative in the settings of high clinical suspicion